2021
DOI: 10.30773/pi.2020.0159
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Health-Related Quality of Life on Suicidal Ideation and Depression among Older Korean Adults: A Cross-Sectional Study

Abstract: Objective The aim of this study was to investigate the prevalence of depression and suicidal ideation among older Korean adults and the predictors of suicidal ideation.Methods We analyzed data from 5,604 Koreans aged 65 or older collected by the Korea National Health and Nutrition Examination Survey in 2012–2016, an annual national, cross-sectional, epidemiologic study of the Korean population. A chi-square test was used to assess differences in socio-demographic characteristics by suicidal ideation. Psycholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Nonetheless, it should be noted that our findings based on cross-sectional study cannot confirm causal relationship between depressive symptoms, anxiety symptoms and HRQoL. Certainly, a study suggested that low HRQoL was associated with depression [ 38 ].…”
Section: Discussionmentioning
confidence: 63%
“…Nonetheless, it should be noted that our findings based on cross-sectional study cannot confirm causal relationship between depressive symptoms, anxiety symptoms and HRQoL. Certainly, a study suggested that low HRQoL was associated with depression [ 38 ].…”
Section: Discussionmentioning
confidence: 63%
“…A previous study on older adults with executive dysfunction showed that age ≥ 75 years, living alone, and low socioeconomic status were associated with suicidal ideation or attempts ( 37 ). In this context, suicidal thoughts can lead to a lower quality of life ( 11 ). In this study, frailty, depression, and cost of living were found to affect the quality of life along with suicide.…”
Section: Discussionmentioning
confidence: 99%
“…It is affected by physical and mental capacities, functional abilities, and environmental aspects, such as social factors. A previous study has reported that HRQoL in older adults is associated with sociodemographic factors ( 8 ) physical health status ( 9 ), nutritional status ( 7 , 10 ), and mental health ( 11 ). However, only a few studies have comprehensively investigated the association between health status and HRQoL among older adults living alone.…”
Section: Introductionmentioning
confidence: 99%